Tingkat Kepuasan Mahasiswa Dan Proses Belajar Mengajar Di Perguruan Tinggi X - Husnayetti Husnayetti (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2012)
This paper is to (1) analyze the level of satisfaction of students in the learning process; (2) analyze the variables that give satisfaction to the students in the learning process, (3) analyze the relation between suitability levels with expected performance provided. This study used a technique Importance Performance Analysis (IPA). The result shows, the level of student satisfaction in general is low. Based on the sequences, the lowest suitability level is the speed and accuracy of employees in resolving student complaints, internet and intranet facilities, availability and completeness of the facilities in the library reading room and lecture hall comfort.